Ginsenoside Rg1 Regulates SIRT1 to Ameliorate Sepsis-Induced Lung Inflammation and Injury via Inhibiting Endoplasmic Reticulum Stress and Inflammation - Qian-Lu Wang; Lei Yang; Yue Peng; Min Gao; Ming-Shi Yang; Wei Xing; Xian-Zhong Xiao (Mediators of Inflammation)
Objectives. To investigate the protective effect of ginsenoside Rg1 on relieving sepsis-induced lung inflammation and injury in vivo and in vitro. Methods. Cultured human pulmonary epithelial cell line A549 was challenged with LPS to induce cell injury, and CLP mouse model was generated to mimic clinical condition of systemic sepsis. Rg1 was applied to cells or animals at indicated dosage. Apoptosis of cultured cells was quantified by flow cytometry, along with ELISA for inflammatory cytokines in supernatant. For septic mice, lung tissue pathology was examined, plus ELISA assay for serum cytokines. Western blotting was used to examine the activation of inflammatory pathways and ER stress marker proteins in both cells and mouse lung tissues. Reactive oxygen species (ROS) level was quantified by DCFDA kit. Results. Ginsenoside Rg1 treatment remarkably suppressed apoptosis rate of LPS-induced A549 cells, relieved mouse lung tissue damage, and elevated survival rate. Rg1 treatment also rescued cells from LPS-induced intracellular ROS. In both A549 cells and mouse lung tissues, further study showed that Rg1 perfusion significantly suppressed the secretion of inflammatory cytokines including tumor necrosis factor- (TNF-) alpha and interleukin- (IL-) 6 and relieved cells from ER stress as supported by decreased expression of marker proteins via upregulating sirtuin 1 (SIRT1). Conclusion. Our results showed that ginsenoside Rg1 treatment effectively relieved sepsis-induced lung injury in vitro and in vivo, mainly via upregulating SIRT1 to relieve ER stress and inflammation. These findings provide new insights for unrevealing potential candidate for severe sepsis accompanied with lung injury.